Hemato-Biochemical Studies in Theileriosis Infected Gir Cows and Jaffrabadi Buffaloes - Brahmbhat, Nilima N.; Dodia, Vaibhavsinh D.; Vasava, Amrita A.; Kumar, Binod; Thakre, Bhupendrakumar J.; Bilwa, Avinash. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
This study was conducted to assess the hemato-biochemical alterations in theileriosis infected Gir cows and Jaffrabadi buffaloes from the southwestern region of Gujarat, India. The prevalence of theileriosis in indigenous bovines was studied by screening 518 blood samples of clinically suspected animals during one year period. Among the screened samples, 85 were found to be Theileria spp. positive microscopically. Overall, significantly higher (p <0.001) incidence of Theileria spp. infection was noted in Gir cattle (25.00%, n = 62) compared to Jaffrabadi buffaloes (8.51%, n = 23). Similarly, higher incidence of theileriosis was recorded in both cattle and buffaloes during rainy season (27.90, 10.20%) followed by summer (23.68, 9.80%) and winter (23.25, 4.16%, respectively). Age-wise, the frequency of theileriosis was more in animals >1 year compared to younger ones <6 months of age, while it was more common in females than males. However, the differences in incidences among different risk-factors were insignificant (p >0.05) in both cattle and buffaloes. Hematological analysis revealed significant (p <0.05) decrease in haemoglobin, hematocrit, red blood cells, lymphocytes, and significant (p <0.01) increase in total leucocyte counts, mean corpuscular volume, mean corpuscular haemoglobin and neutrophil counts. Serum biochemistry revealed significant (p <0.05) increase in AST, ALT, ALP, GGT, total bilirubin and blood urea nitrogen in Theileria infected bovines compared to the control.